Sustainability of German fiscal policy and public debt: Historical and time series evidence for the period 1850-2010 - Heiko T. Burret; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and ifo Institute (CESifo), 2013)
In the last decades, the majority of OECD countries has experienced a continuous increase in public debt. The European debt crisis has prompted a fundamental re-evaluation of public debt sustainability and the looming threat of sovereign debt default. Due to a multitude of large scale events in its past, Germany is far from being an exception: In fact, Germany's peacetime debt-to-GDP (Gross Domestic Product) ratio has never been higher. In this paper, we analyse the sustainability of Germany's public finances against the standard theoretical background using a unique database, retrieved from multiple sources covering the period from 1850 to 2010. Multiple currency crises and external events offer anecdotal evidence, contradicting the historical perception of Germany as the poster child of European public finance. Given these corresponding breaks in time series, the empirical analysis is conducted for the subperiods 1872-1913 and 1950-2010. In addition to an anecdotal historical analysis, we conduct formal tests on fiscal sustainability, including tests on stationarity and cointegration and the estimation of Vector Autoregression (VAR) and Vector Error Correction Models (VECM). While we cannot reject the hypothesis that fiscal policy was sustainable in the period before the First World War, the tests allow for a rejection of the hypothesis of fiscal sustainability for the period from 1950 to 2010. This evidence leads to the conclusion that Germany's public debt is in dire need of consolidation. Albeit a much needed reform, the incompleteness of the German debt brake will have to be addressed in the coming years, in order to ensure that fiscal consolidation actually takes place.
Keywords: H62; H63; 330; public debt; sustainability; time series analysis